The PRODUCT QUALITY ON REPURCHASE INTEREST, WHICH IS MEDIATED BY CUSTOMER SATISFACTION WITH MS GLOW SKINCARE PRODUCTS IN JAMBI CITY: Product Quality, Repurchase Interest , And Customer Satisfaction. - Selvia, Levi; Yacob, Syahmardi; Lubis, Tona Aurora (Journal of Business Studies and Management Review, 2024)
This study investigates the impact of product quality on repurchase intention, with customer satisfaction acting as a mediating variable within the skincare industry. The research focuses on MS Glow skincare users in Jambi, Indonesia. Utilizing Structural Equation Modeling (SEM) with SMART PLS 3.0, data was collected through structured questionnaires distributed among the target population. The findings reveal that product quality significantly influences customer satisfaction, which, in turn, affects repurchase intention. Additionally, customer satisfaction mediates the relationship between product quality and repurchase intention, underscoring its pivotal role in consumer decision-making processes. These insights highlight the necessity for skincare companies to prioritize product quality enhancements to foster customer satisfaction and encourage repeat purchases.